2009
DOI: 10.2109/jcersj2.117.373
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and phase transformation of TiO2 nano-crystals in aqueous solutions

Abstract: A halogen-and acid-free aqueous solution was developed to crystallize anatase TiO2 nano-particles. Spinal or zigzag chains of TiO6 octahedrons were formed from [TiO(C2O4)2] 2-ions. They were then gradually transformed into rutile TiO2 in the solutions. Rearrangement of octahedrons realized aqueous phase transition from anatase to rutile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…It plays the role of bridges between surface OH groups of different octahedra and connects the octahedra closely [30]. After H 2 O molecules are removed from the two OH groups of closely connected TiO 6 octahedra, the integration of octahedra is formed [23]. In addition, for the formation of nanotube in the present study, strongly basic condition is also essential.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…It plays the role of bridges between surface OH groups of different octahedra and connects the octahedra closely [30]. After H 2 O molecules are removed from the two OH groups of closely connected TiO 6 octahedra, the integration of octahedra is formed [23]. In addition, for the formation of nanotube in the present study, strongly basic condition is also essential.…”
Section: Resultsmentioning
confidence: 81%
“…It is well known that both anatase and rutile TiO 2 grow from TiO 6 octahedra, and the phase transition proceeds by the rearrangement of the octahedra. Arrangement of TiO 6 octahedra through face-sharing initiates the anatase phase, while the edge-sharing leads to the rutile phase [23,24]. In addition, the effects of alcohols or polyols on phase transformation have been also observed in other inorganic semiconductor crystal such as ZnS [25].…”
Section: Introductionmentioning
confidence: 98%
“…From the specific reflection, it is concluded that both anatase and rutile phase of TiO2 are produced in the synthesis. [13].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, aqueous solution process was established as next‐generation science and technology. Various structures of SnO 2 , TiO 2 , ZnO, etc. were synthesized in the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aqueous solution process was established as next-generation science and technology. Various structures of SnO 2 , [15][16][17][18][19][20] TiO 2 , [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] ZnO, [39][40][41][42][43][44][45][46][47][48] etc. were synthesized in the solutions.…”
Section: Introductionmentioning
confidence: 99%